2019
DOI: 10.3390/v11121154
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic and Pathogenic Characteristics of QX-Type Avian Infectious Bronchitis Virus Strains Isolated in Southwestern China

Abstract: The QX-type avian infectious bronchitis virus (IBV) is still a prevalent genotype in Southwestern China. To analyze the antigenicity and pathogenicity characteristics of the dominant genotype strains (QX-type), S1 gene sequence analysis, virus cross-neutralization tests, and pathogenicity test of eight QX-type IBV isolates were conducted. Sequence analysis showed that the nucleotide homology between the eight strains was high, but distantly related to H120 and 4/91 vaccine strains. Cross-neutralization tests s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…Coincidently, no obvious gross lesions were observed and viral antigens were not detected by IHC in the proventriculi of chickens infected with the isolate I0305/19, although the isolate I0305/19 can replicate efficiently in the proventriculi by viral titration using 9-day-old SPF chicken eggs. In addition, only very mild respiratory signs were observed in both the commercial broilers and the SPF chickens infected with isolate I0305/19; however, other reports demonstrated that the GI-19 viruses could induce obvious respiratory signs (Liu and Kong et al, 2004;Benyeda et al, 2009;Choi et al, 2009;Zhong et al, 2016;Khanh et al, 2018;Xu et al, 2018;Li et al, 2019;Ren et al, 2019a;Yan et al, 2019). The isolate I0305/19 can replicate efficiently in both the trachea and lungs in the infected SPF chickens, which was demonstrated by viral titration in SPF chicken eggs and viral antigen detection by IHC.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Coincidently, no obvious gross lesions were observed and viral antigens were not detected by IHC in the proventriculi of chickens infected with the isolate I0305/19, although the isolate I0305/19 can replicate efficiently in the proventriculi by viral titration using 9-day-old SPF chicken eggs. In addition, only very mild respiratory signs were observed in both the commercial broilers and the SPF chickens infected with isolate I0305/19; however, other reports demonstrated that the GI-19 viruses could induce obvious respiratory signs (Liu and Kong et al, 2004;Benyeda et al, 2009;Choi et al, 2009;Zhong et al, 2016;Khanh et al, 2018;Xu et al, 2018;Li et al, 2019;Ren et al, 2019a;Yan et al, 2019). The isolate I0305/19 can replicate efficiently in both the trachea and lungs in the infected SPF chickens, which was demonstrated by viral titration in SPF chicken eggs and viral antigen detection by IHC.…”
Section: Discussionmentioning
confidence: 94%
“…GI-19 field strains showed different levels of virulence to SPF chickens in experimental infections. Some strains isolated in China were nonpathogenic to SPF chicken (Yan et al, 2017), while others showed low to high pathogenicity to SPF chickens, with morbidity ranging from 40 % to 100 % and mortality ranging between 10 % and 80 % (Table 1) (Liu and Kong, 2004;Zhong et al, 2016;Yan et al, 2017;Xu et al, 2018;Li et al, 2019;Ren et al, 2019aRen et al, ,2019b. The GI-19 virus strain isolated in Malaysia was also highly virulent to SPF chickens with 100 % morbidity and 41.3 % mortality (Khanh et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nephropathogenic IBV strains include B1648, Aus T, QX-like, 4/91, Holte and Gray [ 6 , 24 , 25 , 32 , 50 ]. The IBV B1648 strain is known to spread from the respiratory tissues via blood monocytes [ 50 ].…”
Section: Ibv Infection Of the Renal Systemmentioning
confidence: 99%
“…Therefore, knowledge of different IBV strains and their pathogenicity is important for establishing sustainable vaccination strategies. Despite several published reviews relevant to IBV pathogenesis [ 18 , 19 , 20 , 21 , 22 ], there is a need for an analysis of information due to the large influx of literature in recent years on the evolving pathogenesis of IBV infection [ 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%